Mechanical overload-induced release of extracellular mitochondrial particles from tendon cells leads to inflammation in tendinopathy - Ziming Chen; Mengyuan Li; Peilin Chen; Andrew Tai; Jiayue Li; Euphemie Landao Bassonga; Junjie Gao; Delin Liu; David Wood; Brendan F. Kennedy; Qiujian Zheng; Ming H. Zheng (Experimental and Molecular Medicine, 2024)
Abstract Tendinopathy is one of the most common musculoskeletal diseases, and mechanical overload is considered its primary cause. However, the underlying mechanism through which mechanical overload induces tendinopathy has not been determined. In this study, we identified for the first time that tendon cells can release extracellular mitochondria (ExtraMito) particles, a subtype of medium extracellular particles (mEPs), into the environment through a process regulated by mechanical loading. RNA sequencing systematically revealed that oxygen-related reactions, extracellular particles, and inflammation were present in diseased human tendons, suggesting that these factors play a role in the pathogenesis of tendinopathy. We simulated the disease condition by imposing a 9% strain overload on three-dimensional mouse tendon constructs in our cyclic uniaxial stretching bioreactor. The three-dimensional mouse tendon constructs under normal loading with 6% strain exhibited an extended mitochondrial network, as observed through live-cell confocal laser scanning microscopy. In contrast, mechanical overload led to a fragmented mitochondrial network. Our microscopic and immunoblot results demonstrated that mechanical loading induced tendon cells to release ExtraMito particles. Furthermore, we showed that mEPs released from tendon cells overloaded with a 9% strain (mEP9%) induced macrophage chemotaxis and increased the production of proinflammatory cytokines, including IL-6, CXCL1, and IL-18, from macrophages compared to mEP0%, mEP3%, and mEP6%. Partial depletion of the ExtraMito particles from mEP9% by magnetic-activated cell sorting significantly reduced macrophage chemotaxis. N-acetyl-L-cysteine treatment preserved the mitochondrial network in overloaded tendon cells, diminishing overload-induced macrophage chemotaxis toward mEP9%. These findings revealed a novel mechanism of tendinopathy; in an overloaded environment, ExtraMito particles convey mechanical response signals from tendon cells to the immune microenvironment, culminating in tendinopathy.